A critical review on the simulations of wind turbine aerodynamics focusing on hybrid RANS-LES methods. (1st November 2017) - Thé, Jesse; Yu, Hesheng
Abstract: Wind energy plays a vital role in the development sustainable energy due to its vast availability, commercially ready technology, low cost, and great contribution to CO2 reduction. Wind turbines account for most of the cost involved in both onshore and offshore wind projects. Therefore, wind turbine aerodynamics is the backbone in the wind energy area as it is directly related to its performance. We first review and discuss available engineering models and the Reynolds-Averaged Navier Stokes (RANS) methods for wind turbine aerodynamics. The widely used momentum method is restricted significantly by the availability of reliable airfoil data and its empiricism. Potential flow methods are limited by its exclusion of viscous effect. RANS methods can produce reasonable integrated quantities, but fail to capture complex flow features such as separation and vortex shedding. The hybrid RANS-LES method (HRLM), which is a technique to bridge the gap between less accurate RANS and more computational costly LES method, is a remedy to turbine aerodynamics in complex flow conditions. We then present existing HRLMs and review their applications to wind turbine aerodynamics. They have obvious advantages over the RANS models in the prediction of flow unsteadiness. Finally, we recommend the best practice guidelines for the HRLM to facilitate and promote the implementation of the HRLMs for an improved understanding of flow physics around wind turbine blades. The enhanced knowledge of complex flow characteristics will further benefit subsequent aeroelastic and aeroacoustic analysis. Therefore, the HRLM is a promising tool for the research and development of wind turbine technology. Graphical abstract: Highlights: Brief survey of available engineering models and the RANS approaches. The HRLM is a bridging computational technique for complex flows. Extensive review of the applications of HRLM to wind turbine aerodynamics. HRLMs are superior to RANS approaches in unsteadiness capture. Best practice guidelines for HRLM application to wind turbine aerodynamics.